Pengaruh Berinteraksi dengan Teman Sebaya terhadap Perkembangan Bahasa Anak Usia Dini (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to determine the influence of peer interaction on the language development of early childhood children in Simpang Gambir Village, Lingga Bayu District. Early childhood is a golden period for language development, which is strongly influenced by the social environment. One of the key components of this environment is peer presence, which plays an essential role in play, communication, and learning. This research uses a quantitative approach with survey and observational methods involving children aged 4–6 years. Data were collected through observation of children's language behaviors during play with peers, as well as interviews with teachers and parents. The results show that children who frequently interact with peers demonstrate more advanced language abilities compared to those who rarely engage in peer interaction. Frequent and quality interactions have been shown to improve speaking skills, expand vocabulary, and enhance sentence structure used by the children. Therefore, it can be concluded that peer interaction has a significant positive effect on early childhood language development.